2022
DOI: 10.1002/suco.202200158
|View full text |Cite
|
Sign up to set email alerts
|

Fragility analysis of existing prestressed concrete bridges under traffic loads according to new Italian guidelines

Abstract: After the 2018 collapse of Morandi highway bridge in Genova, new Italian guidelines (GL) were issued for prioritization of safety evaluations and retrofit interventions on existing bridges. Among several novelties, GL introduced new traffic load models (TLMs) which can be adopted for existing bridges in case of noncompliant safety checks according to the Italian building code (NTC) provisions. In this study, a class of simply supported, beam-type, prestressed concrete bridge decks built between 1970 and 1980 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…This has the combined effect of reducing the overall traffic load on the bridge, but also reducing the eccentricity of this load, with respect to the longitudinal axis of the bridge, thus reducing the demand on the edge beams. Note that, as stated previously, an alternative option for the Transitable safety assessment level would have been to consider a reduction in maximum allowable loads and corresponding traffic load model (for example, as discussed in Miluccio et al 14 ).…”
Section: Assessment Resultsmentioning
confidence: 99%
“…This has the combined effect of reducing the overall traffic load on the bridge, but also reducing the eccentricity of this load, with respect to the longitudinal axis of the bridge, thus reducing the demand on the edge beams. Note that, as stated previously, an alternative option for the Transitable safety assessment level would have been to consider a reduction in maximum allowable loads and corresponding traffic load model (for example, as discussed in Miluccio et al 14 ).…”
Section: Assessment Resultsmentioning
confidence: 99%
“…Many studies refer to linear analyses as they require less computational effort and the results have been validated by years of applications. 3,[14][15][16][17] The application of NLFEAs is more recent, but it has become more common because of the increase in computational power. Numerous studies have been conducted on applications of NLFEAs on RC structures with different aims: safety assessment, 18,19 evaluation of damage effects 20,21 and understanding of the structural behavior.…”
Section: State Of the Art And Research Objectivementioning
confidence: 99%
“…Numerous studies have been conducted over the last years on the safety assessment of existing structures. Many studies refer to linear analyses as they require less computational effort and the results have been validated by years of applications 3,14–17 …”
Section: State Of the Art And Research Objectivementioning
confidence: 99%
“…The decreasing safety levels of existing bridges is such an important topic that the Italian Ministry of Infrastructures and Sustainable Mobility published in 2022, in the new Italian guidelines for the safety assessment of existing bridges [2]. An overview of it and a case-study application on an existing bridge can be found in [3][4][5].…”
Section: Introductionmentioning
confidence: 99%